2019
DOI: 10.1371/journal.pone.0216877
|View full text |Cite
|
Sign up to set email alerts
|

Body fat anthropometric indexes: Which of those identify better high cardiovascular risk subjects? A comparative study in Spanish population

Abstract: Aim To determine the association of body mass index (BMI), waist circumference (WC), waist to hip ratio (WHR), waist to height ratio (WHtr) and Body Shape Index (ABSI) with high cardiovascular risk (CVR), as well as to determine whether how strong are these relationships. Material and methods A cross-sectional study was carried out in Spanish Caucasian adults. 3,456 subjects completed the study, 45.78% males, aged < 65 years and non-diabetic subjects. Anthropometric/bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…Ashwell et al [24], on the basis of a meta-analysis of studies conducted in different ethnic groups, confirmed that, both in males and in females, WHtR was a better screening tool than BMI and WC for adult cardiometabolic risk factors. Similar results were obtained in subsequent studies, which compared various anthropometric indices, including newly devised ones [25,26,27]. Cut-off points for WHtR in the subject population equaled 0.56 for men and 0.54 for women.…”
Section: Discussionsupporting
confidence: 83%
“…Ashwell et al [24], on the basis of a meta-analysis of studies conducted in different ethnic groups, confirmed that, both in males and in females, WHtR was a better screening tool than BMI and WC for adult cardiometabolic risk factors. Similar results were obtained in subsequent studies, which compared various anthropometric indices, including newly devised ones [25,26,27]. Cut-off points for WHtR in the subject population equaled 0.56 for men and 0.54 for women.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to the results of our analysis in men, Davila-Batista et al concluded that the CUN-BAE was the best index for the identification of individuals with hypertension, diabetes, and MetS [35]. Corbatón Anchuelo et al emphasize the advantages of using the WC and WHtR in the identification of cardiometabolic disorders in women [16]. In the Chinese population, the best predictors of cardiometabolic disorders in men and women were the BRI and WHtR [36].…”
Section: Plos Onesupporting
confidence: 86%
“…The early identification of metabolic disorders allows for an early intervention and the prevention of serious consequences. Overweight and obesity indices, calculated based on anthropometric measurements, have found a wide application in the identification of metabolic disorders [13][14][15][16][17][18]. The most significant advantages of anthropometric indices include the following: non-invasiveness, low cost, standardized techniques and simplicity of measurements, and the possibility to apply them on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Visceral fat was a strong point to the risk in alterations to the arterial pressure with p≤0,030 to men and p≤0,004 to women, given that it can provoke the release of pro inflammatory cytokines as interleukin 6 (IL-6), tumor necrosis factor (TNF) and adipokines that are able to reduce the NO levels in the vascular system and provoke reactivity, heightening its constriction (ANCHUELO, MARTÍNEZ-LARRAD, et al, 2019, UCHASOVA, GRUZDEVA, et al, 2018. It is, also, a well referred factor to cardiovascular sickening and arterial hypertension in the scientific literature (BYAMBASUKH, EISENGA, et al, 2019, DAVID, GUIMARÃES, et al, 2019, PICHÉ, POIRIER, et al, 2018, RAPHAEL DAVID, LEMOS SILVA, et al, 2018.…”
Section: Discussionmentioning
confidence: 99%